V for versatility: TRPV4 Ca2+ entry channel plays multiple roles in invadosome regulation. (June 2021) - Mori, Yasuo
Abstract: Several Ca 2+ -permeable cation channels attract attention for their mechanotransducer function to evoke Ca 2+ signals in cell invasion. Vellino et al., have clarified the versatility of the osmo-sensing TRPV4 channel in regulating invadosome functions: TRPV4 detects and integrates multiple cellular and environmental cues, triggering Ca 2+ signals and molecular interactions that modulate coupling between acto-adhesion and extracellular matrix degradation.